Influence of Eccentric Water Injection on Shaft Wall Stability. Issue 3 (February 2019) - Du, Mingze
Abstract: The approach of water injection is an effective way to prevent shaft failure. However, due to the building existence or the need for adding a single water injection hole, the symmetric arrangement of the water injection borehole becomes more and more difficult. Therefore, eccentric water injection becomes a water injection method that has to be used. In this paper, the numerical simulation method was used to study the influence of eccentric water injection on the shaft stability by setting the water pressure and injection position distance from the shaft. The results showed that the larger the water injection pressure was, the smaller the vertical compressive stress on the shaft wall was and the larger the strata uplift was. The farther the injection position from the shaft was, the larger the vertical compressive stress on the shaft wall was. It also showed that the farther injection position distance from the shaft was, the weaker the lateral transfer of water pressure was, and the larger the vertical pressure difference between the water injection side and the opposite side was. Combined with the simulation results and the pre-industrial tests, the optimal water injection engineering parameters were determined as injection pressure of 0.3 MPa with injection position 50 m away from the shaft.